2021
DOI: 10.26630/rj.v15i2.2610
|View full text |Cite
|
Sign up to set email alerts
|

Faktor Risiko Stunting Pada Anak Balita Di Kabupaten Lampung Tengah

Abstract: <em>Stunting is stunted growth in children due to malnutrition. It can affect children's cognitive and physical development, increase the risk of infection, and significantly contribute to child morbidity and mortality. This study aims to analyze the risk factors for stunting in children under five (13-59 months). The study used a case-control design to compare previous exposure to stunting and normal children under five. Measurements and interviews were conducted with 120 children under five and their m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
(52 reference statements)
0
1
0
1
Order By: Relevance
“…The results of this study are in line with the results of previous studies, which showed that there was a significant relationship between access to restrooms and stunting in toddlers. 30,31 However, conditions in the field found that most cases had inadequate latrine access (71,4%)…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study are in line with the results of previous studies, which showed that there was a significant relationship between access to restrooms and stunting in toddlers. 30,31 However, conditions in the field found that most cases had inadequate latrine access (71,4%)…”
Section: Discussionmentioning
confidence: 99%
“…Pengukuran dan wawancara dilakukan terhadap 120 anak balita dan ibunya menunjukkan pengaruh yang signifikan antata balita yang tidak mendapatkan ASI Ekslusif dengan kejadian stunting dengan OR=5,29; 95%CI 2,39-11,68, artinya balita yang tidak mendapatkan ASI Ekslusif 5.29 kali lebih beresiko mengalami stunting. (Kristanti & Fithri, 2021) Penelitian lain yang sejalan dengan penelitian ini, penelitian yang dilakukan oleh Pramulya, Wijayanti, Saparwati tahun 2021 yang bertujuan untuk mengetahui hubungan pemberian ASI eksklusif dengan kejadian stunting di wilayah kerja Puskesmas Selopampang Kabupaten Temanggung menunjukkan 44 balita (47,8%) mengalami stunting, yang tidak diberikan ASI eksklusif sebanyak 38 balita dan yang diberikan ASI eksklusif sebanyak 6 balita. Analisis bivariat menunjukkan bahwa ada hubungan pemberian ASI eksklusif dengan kejadian stunting (p value 0,0001).…”
Section: Analisis Multivariatunclassified